College Students Attitude towards Employment Opportunity - Dr. G.Visvanathan **, K.Subbarayan *, (Journal of Experimental Sciences, 2011)
The generation of productive and gainful employment with decent working condition, on a sufficient scale to absorb our growing labor force must form a critical element in the strategy for achieving inclusive growth. The sample consists of 982 students (458 male and 524 female) chosen from 6 colleges located in various districts of Tamil Nadu. The tool, Attitude towards employment opportunity scale, had been constructed and validated by the investigators. Pilot study was conducted and the reliability has been obtained for the attitude towards employment opportunity scale was 0.83 and the validity of a scale was the intrinsic validity and it was found to be 0.91. Thus the attitude towards employment opportunity scale has been constructed by the Investigators has reliability and validity. There is a significant difference between college students, belong to government college students and private college students in respect of their attitude towards employment opportunity.